Optimal Capital Taxation in Economies with Unionised and Competitive Labour Markets - Erkki Koskela; Ronnie Schöb (Center for Economic Studies and ifo Institute (CESifo), 2002)
According to the existing literature, capital taxes should not be imposed in the presence of optimal profit taxation in either unionised or competitive labour markets. We show that this conclusion does not hold for an economy with both competitive and unionised sectors, where the competitive wage rate provides the outside option for unionised workers. Even with non-distortionary profit taxation it is optimal for such an economy to tax capital if the revenue share of capital in the unionised sector is lower than the revenue share of capital in the competitive sector. This is because taxing capital income reduces employment and lowers the outside option of workers in the unionised sector with the latter effect being stronger. A capital subsidy should be granted if the opposite relationship in terms of revenue shares holds.
Keywords: 330; optimal capital taxation; unionised and competitive labour markets; outside option